THE DEVELOPMENT OF COOPERATION SKILLS OF SENIOR PRESCHOOLERS IN THE EXPERIMENTATION PROCESS - Karuk, Inna; Kolesnik, Kateryna; Prysiazhniuk, Larysa; Kryvosheya, Tetiana; Shykyrynska, Oleksandra; Vyshkivska, Vanda; Komarivska, Nadiia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
The authors of the article consider the importance of cooperation skills as some of soft skills of a person. The significance of developing these skills from preschool age on is emphasized. The influence of children's experimentation on their all-round development and readiness of senior preschool children to study at school is considered. The interrelation between group activities in the process of experimentation and the development of senior preschoolers’ cooperation skills is shown. Based on the observation of children's activities in the process of experimentation, the educator’s participation in this process and the survey of senior preschoolers and educators reveal the aspects of the organization of children’s group activities that have to be improved. The peculiarities of the educator's participation at all stages of the experiment done by senior preschool children in groups are analyzed – during the goal setting, discussion of the experimental procedure, summarizing, as well as during the verbal report on the results of the experiment. Emphasis is placed on the fact that it is important to organize experimentation centres at preschool institutions, which will allow children to freely experiment and form a team to carry out search activities. The psychological and pedagogical conditions for the children's experimentation in groups being organized at preschool institutions by educators for the successful formation of senior preschoolers’ cooperation skills are formulated.